2016
DOI: 10.1099/mic.0.000171
|View full text |Cite
|
Sign up to set email alerts
|

CitA (citrate) and DcuS (C4-dicarboxylate) sensor kinases in thermophilic Geobacillus kaustophilus and Geobacillus thermodenitrificans

Abstract: The thermophilic Geobacillus thermodenitrificans and Geobacillus kaustophilus are able to use citrate or C 4 -dicarboxylates like fumarate or succinate as the substrates for growth. The genomes of the sequenced Geobacillus strains (nine strains) each encoded a two-component system of the CitA family. The sensor kinase of G. thermodenitrificans (termed CitA Gt ) was able to replace CitA of Escherichia coli (CitA Ec ) in a heterologous complementation assay restoring expression of the CitA Ec -dependent citC-lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…29 A BLAST search 30 identified CitA homologues in several Geobacillus species out of which the protein of G. thermoleovorans ( Figure S1) was chosen for further characterization. In the course of this study a highly similar histidine kinase of Geobacillus thermodenitrif icans was reported to function as citrate sensor, 31 thereby confirming that the chosen PAS domain was most likely specific for citrate. The DNA sequence encoding residues 31−161 of GtCitA was cloned into plasmid pIVEX2.4IN 32 to express the PAS domain N-terminally fused to His-tagged immunity protein 7 of Escherichia coli (Im7; see Figure S2).…”
Section: ■ Results and Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…29 A BLAST search 30 identified CitA homologues in several Geobacillus species out of which the protein of G. thermoleovorans ( Figure S1) was chosen for further characterization. In the course of this study a highly similar histidine kinase of Geobacillus thermodenitrif icans was reported to function as citrate sensor, 31 thereby confirming that the chosen PAS domain was most likely specific for citrate. The DNA sequence encoding residues 31−161 of GtCitA was cloned into plasmid pIVEX2.4IN 32 to express the PAS domain N-terminally fused to His-tagged immunity protein 7 of Escherichia coli (Im7; see Figure S2).…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…29 A BLAST search 30 identified CitA homologues in several Geobacillus species out of which the protein of G. thermoleovorans (Figure S1) was chosen for further characterization. In the course of this study a highly similar histidine kinase of Geobacillus thermodenitrif icans was reported to function as citrate sensor, 31 thereby confirming that the chosen PAS domain was most likely specific for citrate.…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…Nitrate was included to support anaerobic growth, glycerol and gluconate as carbon sources that support growth without strong glucose repression. For anaerobic conditions, plates were incubated under N 2 in anaerobic jars, β‐galactosidase activity was determined in 96‐well microtiter plates (Graf et al , ). β‐Galactosidase is given in Miller U, or MU (ΔA 420 min −1 ml −1 OD 570 −1 ) (Miller, ; Graf et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…It is a member of the PAS domain containing HKs which comprise 30 % of all HKs ( 14 ). CitA belongs to a sensor kinase subfamily ( 15 ) of HKs, which can bind to citrate or C 4 -dicarboxylates. This class of sensor HK has two PAS domains, a periplasmic (or extracytoplasmic) ligand binding domain (PASp) and a cytoplasmic transmitter domain (PASc).…”
Section: Main Textmentioning
confidence: 99%